Fennerosquilla heptacantha (Crustacea: Stomatopoda: Squillidae) in South Atlantic Ocean - Lucatelli, Débora (Zootaxa, 2015)
Fennerosquilla is a monotypic genus that belongs to the family Squillidae, which has the highest generic diversity within Stomatopoda. This genus has been recorded in the north Atlantic Ocean, the Gulf of Mexico and Caribbean Sea, between 105 and 458 m depth. The present specimen was collected during the project “Avaliação da Biota Bentônica e Planctônica na porção offshore das Bacias Potiguar e Ceará”, in 2011, from the continental slope region of Brazil. In this expedition Fennerosquilla heptacantha was found at 178–193 m depth, and represents the first record of the species in the south Atlantic Ocean (Rio Grande do Norte State, northeastern Brazil), expanding the southern limit distribution. The specimen is the largest recorded, measuring 149 mm total length. The pigmentation zone on median region of telson and all diagnostic characters are still preserved and agree with the original description. Fennerosquilla heptacantha has a disjunct deep water distribution (more than 100 m) in the tropical western Atlantic, mostly along the continental slope.